The CENPN/STAT3/USP37 signaling axis promotes invasion, migration and metastasis in nasopharyngeal carcinoma - Wang, Yu-Fei; Zou, You; Qiao, Yue-Long; Wu, Li-Zhi; Xu, Shan; Yang, Rui; Jiao, Wo-Er; Chen, Shi-Ming (Frontiers in Oncology, 2025)
BackgroundNasopharyngeal carcinoma (NPC) metastasis is the main cause of poor treatment outcomes and death in nasopharyngeal carcinoma patients. Previously, we reported that centromere protein N (CENPN) is closely related to the pathogenesis, radiotherapy resistance and chemotherapy resistance of nasopharyngeal carcinoma, but the relationship between CENPN and nasopharyngeal carcinoma metastasis and its molecular mechanism are still unclear.MethodsTwo nasopharyngeal carcinoma cell lines with stable CENPN knockdown and overexpression were constructed, and changes in their proliferation, invasion and metastasis capacity were detected. Transcriptome sequencing after CENPN knockdown was performed to screen downstream genes regulated by CENPN. The effects of CENPN on the ubiquitin-specific peptide 37 (USP37) transcription were detected via western blotting and qRT-PCR. A bioinformatics analysis revealed that signal transducer and activator of transcription 3 (STAT3) may regulate USP37 transcription. The interaction between CENPN and STAT3 was detected via coimmunoprecipitation, GST pull-down and protein truncation tests. Luciferase reporter, ChIP and mutation assays were used to detect the regulatory effects of STAT3 on USP37 expression. The effect of CENPN on nasopharyngeal carcinoma metastasis in vivo was tested in nude mice. The expression of CENPN, STAT3 and USP37 in metastatic tumors from nude mice and human nasopharyngeal carcinoma tissues was verified by immunohistochemistry and immunofluorescence staining.ResultsThe invasion and migration capacities of nasopharyngeal carcinoma cells decreased significantly after CENPN knockdown, whereas the overexpression of CENPN significantly promoted the invasion and metastasis abilities of nasopharyngeal carcinoma cells. Transcriptome sequencing showed that USP37 transcription was significantly inhibited after CENPN knockdown, and bioinformatics predicted STAT3 as a potential transcription factor for USP37. Experiments confirmed that CENPN binds directly to STAT3, which regulates USP37 transcription. In vivo studies demonstrated a reduced number of liver metastatic tumors in mice injected with CENPN knockdown cells, with decreased expression levels of CENPN, p-STAT3, and USP37. Nonmetastatic NPC tissues also had lower levels of these proteins compared to metastatic tissues.ConclusionsCENPN directly binds to STAT3 and promotes STAT3 phosphorylation and nuclear translocation to regulate USP37 transcription, thus promoting the invasion and metastasis of nasopharyngeal carcinoma. The CENPN/STAT3/USP37 axis is expected to be a new target for nasopharyngeal carcinoma treatment.